Dystopian Transformations and Character Construction in Young Adult Science Fiction Lauren Olivers’ Delirium - Lalitya Putri Noorullya (Universitas Pendidikan Indonesia (UPI), 2014)
The present study entitled Dystopian Transformations and Character Construction in Young Adult Science Fiction Lauren Olivers’ Delirium focuses on the issue of dystopian transformations and character construction. The study investigates the main character, Lena; character construction in the novel; and the contribution of character constellations in the construction of Lena’s characterization. The study was conducted within a descriptive text analysis by applying a qualitative method and is framed by theoretical frameworks of narrative theory (Rimmon-Kenan, 1983) and young adult literature science fiction and dystopia (Bradford, Mallan, Stephens McCallum, 2008). The results demonstrate that Lena’s characterization is constructed through two factors. These factors are the atmosphere of dystopian transformations and constellation characters which give both positive and negative effects to Lena’s characterization.Keywords: Science Fiction, Dystopia, Young Adult Dystopia, Characterization, Narrative Theory, Constellation Character